Emergency Remote Learning at ESS-UFF in the context of the pandemic - Sakurada, Priscila Keiko Cossual; Santos, Ebe Campinha dos (Argumentum, 2022)
This article presents the political-pedagogical coping strategies employed by ESS-UFF in Emergency Remote Learning (ERL) and analyzes the disputes within educational projects within Public Universities in the context of antagonistic class relations in Brazilian capitalist society. Then, linked to this explanation, we will address the implementation of ERL in Public Universities, presenting data that supports the strategies outlined by ESS to counter the integral transposition of the curriculum for this mode of learning. Finally, reflecting this experience, it demonstrates the need to pay attention to the developments of ERL in Public Universities, face-to-face teaching, and the formative process in Social Work. This article is based on bibliographic and documentary research, adopting the Marxist theoretical perspective.